Produção de aroma de coco por Trichoderma harzianum utilizando bagaço de cana - Calasans, Patricia Nunes (2012)
Biotechnology is inserted within the search for new products and processes, thus becoming an important tool in the development of biotechnological natural aroma production processes. Flavors compounds obtained from these processes represent a very promising and viable way of production for industries mainly due to the increase of consumer preference for natural food additives and products. Many microorganisms isolated from various environments have potential to synthesize flavors compounds when cultivated in an appropriate culture medium. Fermentation processes allow the use of agro-industrial wastes in which disposal on the environment may cause serious pollution issues. The residues composition, mostly the carbon source, allows the growth of microorganisms and the production of higher aggregate value compounds. The aim of this work is the to produce and quantify the 6-pentyl-á-pyrone lactone, responsible for the coconut-like aroma, by using agro-industrial waste as support and the filamentous fungus Trichoderma harzianum. Initially three agro-industrial wastes (sugarcane bagasse, coconut shell powder and cassava bagasse) were tested concerning the aroma production. Then the gas chromatography coupled to headspace extraction technique provided the quantitative and qualitative analysis of the lactone. Through the chromatogram area, the 4040 strain of Trichoderma fungus and the cassava bagasse were selected as culture medium. The latter was studied by the physical chemistry aspect. The tests done in order to evaluate the microorganism lactone toxic level did not show a complete inhibition in cell growth, only a few spores. The total factorial design in two levels was applied to verify the influence of the nutrients concentration (C/N) and temperature in the production of 6-pentyl-á-pyrone. The largest production of aroma compound resulted in 3.78 mg/g MS at the 7th culture day. The linear and quadratic terms related to temperature were important to the proposed model at a 95% trust level for aroma maximum concentration, by setting values between 25 and 28°C. The C/N ratio effect and the interaction between these two variables were not statistically meaningful.